2016
DOI: 10.1117/12.2223986
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of atmospheric parameters from time-lapse imagery

Abstract: A time-lapse imaging experiment was conducted to estimate various atmospheric parameters for the imaging path. Atmospheric turbulence caused frame-to-frame shifts of the entire image as well as parts of the image. The statistics of these shifts encode information about the turbulence strength (as characterized by C n 2 , the refractive index structure function constant) along the optical path. The shift variance observed is simply proportional to the variance of the tilt of the optical field averaged over the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…The exact amount of underestimation will depend on the block size, the particular C 2 n ðzÞ profile, and optical parameters. 36,37 Notwithstanding this, we have found that a fixed block size of B ¼ 15 pixels is effective for the range of turbulence conditions used in the simulated imagery. Furthermore, our results show that the corresponding residual RMS tilt factor is approximately a constant β ¼ 0.1 in the simulated imagery.…”
Section: Block-matching and Wiener Filtering Turbulence Mitigationmentioning
confidence: 89%
See 3 more Smart Citations
“…The exact amount of underestimation will depend on the block size, the particular C 2 n ðzÞ profile, and optical parameters. 36,37 Notwithstanding this, we have found that a fixed block size of B ¼ 15 pixels is effective for the range of turbulence conditions used in the simulated imagery. Furthermore, our results show that the corresponding residual RMS tilt factor is approximately a constant β ¼ 0.1 in the simulated imagery.…”
Section: Block-matching and Wiener Filtering Turbulence Mitigationmentioning
confidence: 89%
“…Thus, any block-based estimate will tend to underestimate the true tilt for a given point, by virtue of the spatial averaging effect. 36,37 Thus, we define a partial tilt correction operator ass −1 k;α ðx; yÞ½•. Applying this to the SE frames, and applying an ensemble mean, yields E Q -T A R G E T ; t e m p : i n t r a l i n k -; e 0 2 4 ; 6 3 ; 2 9 4 fðx; yÞ ¼ hs −1 k;α ðx; yÞ½f k ðx; yÞi ¼ g α ðx; yÞ Ã h SE ðx; yÞ Ã zðx; yÞ ¼ h α ðx; yÞ Ã zðx; yÞ: (24) This result gives the rational for using h α ðx; yÞ as the degradation blur model for fully or partially tilt corrected imagery.…”
Section: Observation Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Some image-based methods have been developed that use a standard camera with specialized targets or sources [12,13]. Other methods are scene-based and use only the natural imagery acquired by an imaging sensor [14][15][16][17][18][19][20]. Methods that explicitly address camera or scene motion include [9,21].…”
Section: Introductionmentioning
confidence: 99%